Reconstruction of the Anterior External Auditory Canal With Mastoid Cortex Autologous Bone Graft. Issue 10 (December 2021) - Lovett, Braeden L.; Shearer, Sarah C.; Kim, H. Jeffrey
Abstract : Objective: To describe the surgical management of temporomandibular joint (TMJ) herniation with external auditory canal (EAC) reconstruction using autologous bone grafting from the mastoid cortex. Study Design: Retrospective case series. Setting: A tertiary university medical center. Patients: Three patients who presented to our Otolaryngology clinic with evidence of TMJ herniation through an anterior EAC defect, both on otoscopy and computed tomography (CT) imaging. Interventions: Reconstruction of the anterior EAC with mastoid cortex bone grafting using an endaural approach. Main Outcome Measures: Successful reconstruction of anterior EAC bony defect without recurrence of herniation. Results: All three patients presented with otalgia, hearing loss, and either tinnitus or a clicking sensation with jaw movement. Etiologies for TMJ herniation included osteoradionecrosis following external beam radiation therapy for head and neck carcinoma and iatrogenic injury following multiple tympanoplasties and canalplasties. A mastoid cortex bone graft was placed and secured anterior to the bony EAC defect through an endaural approach. Two patients wore a dental retainer postoperatively to keep the condyle in an open position. After reconstruction, patients reported an improvement in their presenting symptoms. There was no recurrence of TMJ herniation in all cases after 1, 4, and 9 years. Conclusions: Anterior EAC reconstruction with autologous bone grafting can be an effective definitive treatment in TMJ herniation. To our knowledge, this is the first report of the use of bone grafting to reconstruct the canal defect in TMJ herniation. Level of Evidence: V.